Critical race judgments : re-written U.S. court opinions on race and the law / edited by Bennett Capers, Devon Carbado, R. A. Lenhardt, Angela Onwuachi-Willig. - Capers, Bennett, 1966-; Carbado, Devon W.; Lenhardt, Robin A.; Onwuachi-Willig, Angela (Cambridge University Press, 2022)
By re-writing US Supreme Court opinions that implicate critical dimensions of racial justice, Critical Race Judgments demonstrates that it's possible to be judge and a critical race theorist. Specific issues covered in these cases include the death penalty, employment, voting, policing, education, the environment, justice, housing, immigration, sexual orientation, segregation, and mass incarceration. While some rewritten cases - Plessy v. Ferguson (which constitutionalized Jim Crow) and Korematsu v. United States (which constitutionalized internment) - originally focused on race, many of the rewritten opinions - Lawrence v. Texas (which constitutionalized sodomy laws) and Roe v. Wade (which constitutionalized a woman's right to choose) - are used to incorporate racial justice principles in novel and important ways. This work is essential for everyone who needs to understand why critical race theory must be deployed in constitutional law to uphold and advance racial justice principles that are foundational to US democracy.